Monitoring Poverty Trends and Exploring Poverty Dynamics in Ireland - Layte, Richard; Maitre, Bertrand; Nolan, Brian; Watson, Dorothy; Whelan, Christopher T; Williams, James; Casey, Barra (ESRI, 2001)
The paper on Monitoring Poverty Trends is the latest report in the annual series commissioned by the Department of Social, Community and Family Affairs. It attempts to assess progress in reaching the national targets in relation to poverty reduction. This year's report focused in particular on the processes leading individuals and households to enter, and to exit from, situations of poverty. It discovered that, as has been found in other countries, it is very important when assessing the severity of poverty to take into account its relative degree of permanence or transience. Overall, the paper concluded that, based on the measure reflecting consistent poverty which incorporates assessment of both income and deprivation, the situation in Ireland had shown appreciable improvement over the last number of years.